Association between opioid dose escalation and time to death in a comfort measures only population. (16th October 2020) - Abraham, Dana L; Hernandez, Inmaculada; Ayers, Gina T; Pruskowski, Jennifer A
Abstract: Purpose: Opioids are crucial to the relief of pain and dyspnea experienced by patients dying in the hospital setting; however, there are concerns about the association of opioid dosage with hastened death via opioid-induced respiratory depression, and there is little published evidence regarding the association between opioid dose escalation and time to death in the inpatient comfort measures only (CMO) population. Methods: The medical records of adult patients admitted to 2 hospitals who had an active CMO order at the time of death and received opioid dose escalations after CMO pronouncement were assessed in a retrospective cohort study. Patients were categorized into higher and lower opioid dose escalation groups according to an institutional palliative care symptom guide. A Cox proportional hazards model was constructed to test the associations between dose escalation group, patient sex, opioid naivety, palliative care consultation, and opioid dosage after CMO pronouncement (independent variables) and time to death (dependent variable). Results: In the 71-patient cohort, 39 patients (54.9%) were male and 32 (45.1%) were female. The mean (SD) age of patients was 67.2 (16.6) years. Higher dose escalation ( n = 46, 64.8%) was associated with a nonsignificant decrease in survival time compared to lower dose escalation ( n = 25, 35.2%), with a mean difference in time to death of 19.8 hours (hazard ratio [HR], 1.67; 95% confidence interval [CI], 0.94-2.97). Receipt of a palliative care consult ( n = 56, 78.9%) during the final hospital visit was associated with increased survival time (mean difference, 20.1 hours; HR, 0.32; 95% CI, 0.16-0.63). Conclusion: Time to death in an inpatient CMO population was not significantly associated with the degree of opioid dose escalation.